2018
DOI: 10.1515/jpm-2018-0295
|View full text |Cite
|
Sign up to set email alerts
|

Small for gestational age and extremely low birth weight infant outcomes

Abstract: Background Small for gestational age (SGA) infants are less likely to develop respiratory distress syndrome (RDS), but more likely to develop bronchopulmonary dysplasia (BPD) and have a higher mortality. Our aim was to focus on outcomes of those with a birth weight less than or equal to 750 g. Methods The mortality, BPD severity, necrotising enterocolitis (NEC), home oxygen requirement and length of hospital stay were determined according to SGA status of all eligible infants in a 5-year period admitted withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
3
15
1
Order By: Relevance
“…17,18,28,29 Infants born SGA are at greater risk of severe BPD and death, and pulmonary hypertension has been independently associated with increased risk of mortality in premature infants with BPD. [30][31][32][33][34][35][36] Murthy et al 17 demonstrated that infants born at <32 weeks' gestation with severe BPD complicated by pulmonary hypertension had three times increased risk of tracheostomy or death. Although the mechanisms remain uncertain, it is probable that the increased rates of mortality are due to adverse effects on the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,28,29 Infants born SGA are at greater risk of severe BPD and death, and pulmonary hypertension has been independently associated with increased risk of mortality in premature infants with BPD. [30][31][32][33][34][35][36] Murthy et al 17 demonstrated that infants born at <32 weeks' gestation with severe BPD complicated by pulmonary hypertension had three times increased risk of tracheostomy or death. Although the mechanisms remain uncertain, it is probable that the increased rates of mortality are due to adverse effects on the pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In our setting, it was possible to exclude this bias and to clearly delimit the patient groups due to the defined periods of the respective treatment methods. With a median patient weight of 640 g and a gestational age of 24.3 weeks, the patient cohort of our study differs significantly from the data previously published and also focuses on surgical interventions that were carried out on patients with a weight of less than 1000 g. In the literature, the general mortality rate of ELBW infants is stated to be from 20 to 50% depending on the author, although it differs considerably even within the group, depending on weight and gestational age [13][14][15]. Therefore, we also determined the CRIB score to classify the general mortality risk of premature infants in order to further validate our results in both patient groups [6,16].…”
Section: Discussionmentioning
confidence: 99%
“…The iNO trials conducted to date in preterm infants have included a range of patient populations (gestational ages ranging from 24-28 weeks to <34 weeks) and different strategies (initiation of iNO at different times after birth and duration of iNO administration), making it difficult to interpret overall study results [5][6][7][8][9][10][11][12][13][14]. Small for gestational age infants are at high risk of adverse outcomes including severe BPD [31], increased rehospitalization, and need for chest medications at follow-up [32]. There is no evidence, however, from randomized controlled trials that iNO will particularly benefit this group.…”
Section: Discussionmentioning
confidence: 99%